Influence of Information Technology and Working Time on the Competency and Quality of Administration Services, Hasanuddin University - Ruth Epi Lobo; Musran Munizu; Yunus Amar (Magister Management, Hasanuddin University, 2020)
This study aims to analyze the effect of information technology and tenure on the competence and quality of administrative services at Hasanuddin University. This type of research uses this type of quantitative research is a type of research which is a type of research with the researcher as the decision-maker for what research will be carried out, compiling specific questions, limiting questions, collecting measurable data from participants, analyzing numbers using statistics, conducting an impartial investigation, in objective ways. In analyzing data, researchers collect, classify, analyze, and interpret data in order to provide a clear picture of the problem under study. The results showed that information technology partially has a positive and significant effect on competence, tenure partially has a positive and significant effect on competence, information technology partially has a positive and significant effect on service quality, tenure partially has a positive and significant effect on service quality, Competence partially has a positive and significant effect on service quality, Information technology partially has a positive and significant effect on the quality of administrative services through competence, then tenure partially has a positive and significant effect on the quality of administrative services through competence.